Síndrome de Lemièrre y Leptospirosis: Dos Entidades Simultáneas - Catarina Cabral; Inês Santos; Joana Vaz; Sara Rocha (Galicia Clínica)
Lemièrre syndrome arises after an oropharyngeal infection, with extension to the nearby structures and the carotid sheath, resulting in thrombophlebitis of the internal jugular vein. It is mainly caused by bacteria from the Fusobacterium genus, resulting in bacteriemia and systemic disease, possibly involving the kidneys, liver and blood. Leptospirosis is a zoonotic infection, transmitted through contact with infected water or soil or through direct contact with infected animals. Rats are the main reservatory. Weil’s disease is the severe form of leptospirosis, causing acute kidney injury, hepatic lesion and pulmonary hemorrhage. The authors present a case where these two entities were detected, showing the difficulties associated with the diagnosis and management of associated complications.